2020
DOI: 10.3390/agronomy10040476
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Environmental Covariates and Ceylon Tea Cultivation in Sri Lanka

Abstract: How the current distribution of tea cultivation is influenced by specific environmental conditions in Sri Lanka is yet to be explored. Therefore, this study aims to assess the differences between tea and non-tea growing areas with respect to climatic and topographic covariates, and to determine the major covariates that control tea distributions. Climatic data of temperature and rainfall were extracted from WorldClim-Global Climate Data; the elevation, slopes, and aspects were obtained from Global Multi-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Annual mean temperature (BIO1) was the key indicator for determining the suitability of tea habitat in Kenya and China ( Figure 1) and ( Table 2). Similar to the findings of previous studies, the highest probability of tea occurrence in the four countries was related to areas having a mean annual temperature around 20 • C [16,58]. Annual precipitation (BIO12) emerged as the strongest range predictor to determine current and future suitable habitats for tea in India and Kenya as precipitation is critical and plays an important role in sustaining tea cultivation [16].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Annual mean temperature (BIO1) was the key indicator for determining the suitability of tea habitat in Kenya and China ( Figure 1) and ( Table 2). Similar to the findings of previous studies, the highest probability of tea occurrence in the four countries was related to areas having a mean annual temperature around 20 • C [16,58]. Annual precipitation (BIO12) emerged as the strongest range predictor to determine current and future suitable habitats for tea in India and Kenya as precipitation is critical and plays an important role in sustaining tea cultivation [16].…”
Section: Discussionsupporting
confidence: 82%
“…The monsoonal climate, alternate wet and dry seasons and the high elevation of subtropical mountains in China, India, and Sri Lanka appear to provide above optimal conditions for tea cultivation [15]. A successful tea cultivation is highly dependent on climatic factors [16]. Abrupt climate change has been recognised as the foremost environmental issue for tea systems and the tea plant experiences the multi-decadal impacts of climate change all over the world as it has a long lifespan [17].…”
Section: Introductionmentioning
confidence: 99%
“…Geographical environment has a significant impact on the growth of tea plants, which is mainly influenced by light intensity, light duration, rainfall, etc. (Jayasinghe et al., 2020; Liu et al., 2013). Research has shown that phospholipid content increases with light exposure and thus, when the level of chlorophyll derivatives is lower (Jaakola & Hohtola, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the concentration of caffeine and polyphenol in tea increases with altitude, whereas an increase in light intensity decreases the content of AAD and caffeine (Akiko et al, 2011;Song et al, 2012;Zhang et al, 2014). Temperature, light intensity, and hours of sunlight vary greatly depending on the geographical location and play a vital role in plant growth and quality formation (Jayasinghe et al, 2020;Liu et al, 2013). Kang et al (2019) analyzed the aromas of the world's four most famous black teas and found that methyl salicylate (Ceylon), (E)−2-octenal (Assam), benzeneacetaldehyde (Keemun), and linalool and trans-linalool oxide (furanoid) (Darjeeling) might be the most definitive odorants in the corresponding tea categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation